Mental Illness and Unhappiness - Richard Layard; Dan Chisholm; Vikram Patel; Shekhar Saxena (Institute for the Study of Labor (IZA), 2013)
This paper is a contribution to the second World Happiness Report. It makes five main points. 1. Mental health is the biggest single predictor of life-satisfaction. This is so in the UK, Germany and Australia even if mental health is included with a six-year lag. It explains more of the variance of life-satisfaction in the population of a country than physical health does, and much more than unemployment and income do. Income explains 1% of the variance of life-satisfaction or less. 2. Much the most common forms of mental illness are depression and anxiety disorders. Rigorously defined, these affect about 10% of all the worlds population and prevalence is similar in rich and poor countries. 3. Depression and anxiety are more common during working age than in later life. They account for a high proportion of disability and impose major economic costs and financial losses to governments worldwide. 4. Yet even in rich countries, under a third of people with diagnosable mental illness are in treatment. 5. Cost-effective treatments exist, with recovery rates of 50% or more. In rich countries treatment is likely to have no net cost to the Exchequer due to savings on welfare benefits and lost taxes. But even in poor countries a reasonable level of coverage could be obtained at a cost of under 2 per head of population per year.
Keywords: I10; I14; I18; 330; mental illness; welfare benefits; healthcare costs; life-satisfaction